Pipe drafting and design - Parisher, Roy A. (Oxford : Gulf Professional, 2011)
Pipe Drafting and Design, Third Edition provides step-by-step instructions to walk pipe designers, drafters, and students through the creation of piping arrangement and isometric drawings. It includes instructions for the proper drawing of symbols for fittings, flanges, valves, and mechanical equipment. More than 350 illustrations and photographs provide examples and visual instructions. A unique feature is the systematic arrangement of drawings that begins with the layout of the structural foundations of a facility and continues through to the development of a 3-D model. Advanced chapters discuss the use of 3-D software tools from which elevation, section and isometric drawings, and bills of materials are extracted. Covers drafting and design of pipes from fundamentals to detailed advice on the development of piping drawings, using manual and CAD techniques 3-D model images provide an uncommon opportunity to visualize an entire piping facility Each chapter includes exercises and questions designed for review and practice New to this edition: A large scale project that includes foundation location, equipment location, arrangement, and vendor drawings Updated discussion and use of modern CAD tools Additional exercises, drawings, and dimensioning charts to provide practice and assessment New set of Powerpoint images to help develop classroom lectures.
Chapter 1. Overview of Pipe Drafting and Design -- Chapter 2. Steel Pipe -- Chapter 3. Pipe Fittings -- Chapter 4. Flange Basics -- Chapter 5. Valves -- Chapter 6. Mechanical Equipment -- Chapter 7. Flow Diagrams and Instrumentation -- Chapter 8. Codes and Specifications -- Chapter 9. Equipment Layout -- Chapter 10. Piping Arrangement Drawings, Sections, and Elevations -- Chapter 11. Standard Piping Details -- Chapter 12. Piping Systems -- Chapter 13. Piping Isometrics -- Chapter 14. Building 3D Piping Models -- Chapter 15. Project Coordination.
Previous ed.: 2002.
Includes index.
Keywords: Piping -- Drawings; Electronic books; Drawings